Analysis of Detection of Growth and Development In Gross Motor Toddlers (Case Study of Babies Aged 6 Months Cannot Pronning, Roll and Crooked) - Lati Nurliana Wati Fajzrina; Nur Cahyati Ngaisah; Ira Pratamasari (JOYCED: Journal of Early Childhood Education, 2022)
The analytical method of detecting growth and development carried out on children is not solely without reasons and benefits, apart from detecting whether there is a disturbance in their growth and development or not, as well as early prevention in children so that parents are able to minimize the occurrence of problems and obstacles to the growth and development of the baby. The number of respondents used is one, because this research is in the form of a field case study of toddlers aged 6 months who were conducted at AMC Metro Hospital with sources from the child development polyclinic doctor, and the baby's parents. Data obtained through direct observation, interviews and documentation. Data analysis was carried out to limit matters outside the subject matter of the study so that it focuses on the main topic. The results of the research showed that toddlers experienced gross motoric problems, namely not being able to lie on their stomach, rolling over (turning over and then lying on their backs), and tilting caused by several factors including the birth process by cesarean section, breastfeeding was replaced with formula milk, and lack of stimulus from other people. old. The solution that can be given is to carry out routine checks on child growth and development polyclinics and independent stimulation at home using the KIA, KPSP, DDTK/SDIDTK guide books, as a reference in an effort to overcome problems that occur in these babies.